A Strategy for Hospital Pharmacists to Control Antimicrobial Resistance (AMR) in Japan - Yukihiro Hamada; Fumiya Ebihara; Ken Kikuchi (MDPI AG, 2021)
In Japan, there is concern regarding the relation between the inappropriate use of antibiotics and antibiotic resistance (AMR). Increased bacterial resistance is due in part to the inappropriate use of antimicrobial agents. The support of the pharmacist becomes important, and there is growing interest in antimicrobial stewardship to promote the appropriate and safe use of antimicrobials needed for the optimal selection of drugs, doses, durations of therapy, therapeutic drug monitoring (TDM), and implementations of cost containment strategies in Japan. Pharmacists should strive to disseminate the concept of "choosing wisely" in relation to all medicines, implement further interventions, and put them into practice. In this article, we present data for antimicrobial stewardship and Japan's AMR action plan, focusing on how pharmacists should be involved in enabling physicians to choose antimicrobials wisely.